1974
DOI: 10.1161/01.res.34.4.435
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limit of Autoregulation of Cerebral Blood Flow in the Baboon

Abstract: The upper limit of autoregulation of cerebral blood flow was studied in ten young baboons. Blood pressure was increased by infusing angiotensin, and cerebral blood flow was measured by the intracarotid 133 xenon injection method. Autoregulation was maintained until blood pressure was 30-40% above resting values. At this blood pressure level, cerebrovascular resistance reached a maximum. Any additional increase in blood pressure resulted in an increase in cerebral blood flow and a decrease in cerebrovascular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
2

Year Published

1978
1978
2004
2004

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(60 citation statements)
references
References 28 publications
(30 reference statements)
6
52
0
2
Order By: Relevance
“…7 Howev er, recent studies have suggested that it may not be regions of vessel narrowing which are at fault but areas of abnormal vasodilation that represent a "break through" of autoregulation. 8 These latter observations suggest that there are regions of resistance vessels where smooth muscle contractility is overcome by in creased intraluminal pressure, leading to vascular damage and subsequent cerebral edema. CBF studies in patients with acute hypertension have documented areas of increased CBF and have been used to support the "breakthrough" hypothesis.…”
Section: Pathogenesismentioning
confidence: 99%
“…7 Howev er, recent studies have suggested that it may not be regions of vessel narrowing which are at fault but areas of abnormal vasodilation that represent a "break through" of autoregulation. 8 These latter observations suggest that there are regions of resistance vessels where smooth muscle contractility is overcome by in creased intraluminal pressure, leading to vascular damage and subsequent cerebral edema. CBF studies in patients with acute hypertension have documented areas of increased CBF and have been used to support the "breakthrough" hypothesis.…”
Section: Pathogenesismentioning
confidence: 99%
“…12,30,31 For obvious reasons, the upper limit of sCA cannot be studied in (normotensive) humans, but in normotensive baboons, it ranges between 120 and 150 mm Hg. 13 In humans with untreated severe chronic hypertension, the lower limit of sCA is shifted rightward to Ϸ115 mm Hg. 11,12 Data on the upper limit of sCA are limited in that it was determined in only 3 hypertensive baboons and was found to be shifted rightward (between 155 and 169 mm Hg).…”
Section: Study Limitationsmentioning
confidence: 99%
“…11,12 For obvious reasons, the upper limit of CA has not been determined in normotensive or hypertensive humans. It was located between 120 and 150 mm Hg 13 in normotensive baboons and between 155 and 170 mm Hg in chronic hypertensive baboons. 14 A moderate reduction in BP with SNP in normotensive subjects does not influence CBF, 15 but to the best of our knowledge, no human studies specifically tested the assumption that CA is impaired in patients with malignant hypertension.…”
mentioning
confidence: 97%
“…These abnormalities include increased cerebral vascular permeability to dye and proteins, 1 ' 2 a loss or "breakthrough" of autoregulation, and forced dilation of the arterial vasculature, which imparts a "sausage-string" appearance. 3 - 4 Additionally, we and our colleagues have shown that following acute hypertension induced by pressor agents or experimental traumatic brain injury, abnormalities of the cerebral arterioles are caused by oxygen radicals formed during increased arachidonic acid metabolism. 5 - 7 The abnormalities include sustained dilation, decreased reactivity to hypocapnia, endothelial leFrom the Department of Pharmacology and Toxicology, Medical College of Virginia, Virginia Commonwealth University, Richmond, Va.…”
mentioning
confidence: 99%